EFEKTIFITAS UNDANG-UNDANG NO 11 TAHUN 2008 TENTANG INFORMASI DAN TRANSAKSI ELEKTRONIK SEBAGAI UPAYA PENANGGULANGAN TINDAK ASUSILA BERBASIS TEKNOLOGI (CYBERSEX) - Muhamad Ilham Nur; Febri Jaya (Ensiklopedia of Journal, 2022)
Abstract: Cybersex is an intimate activity carried out through electronic media. The nature of this Cybersex act itself is a non-violence crime where this crime causes the victim to be invisible or invisible, thereby reducing the fear of this crime. even though the consequences of cybersex itself are very large. In order to protect the victims and deter the perpetrators of this cybersex act, good laws and regulations are needed. In this case, Law No. 11 of 2008 concerning information and electronic transactions is the main regulation in mediating cybersex problems that are happening in society. However, whether legislation no. 11 of 2008 concerning information and electronic transactions has been efficient in tackling cybersex problems that occur in the community or is the regulation made only as a mere formality and has not been able to become a government effort in tackling cybersex actions. The purpose of this study was to examine the efficiency of Law No. 11 of 2008 concerning information and electronic transactions in dealing with cybersex problems. In this study, the researchers used a descriptive analytical method, which relates the current rules and relates to the problems that the researcher has described. This research examines the government's efforts, inhibiting factors and the application of sanctions as social control which is linked to Law No. 11 of 2008 concerning information and electronic transactions.Keywords: Efficient, Law, Cybersex.